Immediate Post-operative Enterocyte Injury, as Determined by Increased Circulating Intestinal Fatty Acid Binding Protein, Is Associated With Subsequent Development of Necrotizing Enterocolitis After Infant Cardiothoracic Surgery - Watson, John D.; Urban, Tracy T.; Tong, Suhong S.; Zenge, Jeanne; Khailova, Ludmilla; Wischmeyer, Paul E.; Davidson, Jesse A. (Frontiers in Pediatrics, 2020)
Objectives: 1) Measure serial serum intestinal fatty acid binding protein levels in infants undergoing cardiac surgery with cardiopulmonary bypass to evaluate for evidence of early post-operative enterocyte injury. 2) Determine the association between immediate post-operative circulating intestinal fatty acid binding protein levels and subsequent development of necrotizing enterocolitis. Design: Observational cohort study. Intestinal fatty acid binding protein was measured preoperatively, at rewarming, and at 6 and 24 hours post-operatively. Percent of goal enteral kilocalories on post-operative day 5 and episodes of necrotizing enterocolitis were determined. Multivariable analysis assessed for factors independently associated with clinical feeding outcomes and suspected/definite necrotizing enterocolitis. Setting: Quaternary free-standing children's hospital pediatric cardiac intensive care unit. Patients: 103 infants less than 120 days of age undergoing cardiothoracic surgery with cardiopulmonary bypass.Interventions: None. Results: Median pre-operative intestinal fatty acid binding protein level was 3.93ng/ml (range 0.24-51.32). Intestinal fatty acid binding protein levels rose significantly at rewarming (6.35ng/ml; range 0.54-56.97; p=0.008), continued to rise slightly by 6hr (6.57ng/ml; range 0.75-112.04; p=0.016), then decreased by 24hr (2.79ng/ml; range 0.03-81.74; p<0.0001). Sixteen subjects (15.7%) developed modified Bell criteria Stage 1 necrotizing enterocolitis and 9 subjects (8.8%) developed Stage 2 necrotizing enterocolitis. Infants who developed necrotizing enterocolitis demonstrated a significantly higher distribution of intestinal fatty acid binding protein levels at both 6hr (p=0.005) and 24hr (p=0.005) post-operatively. On multivariable analysis, intestinal fatty acid binding protein was not associated with percentage of goal enteral kilocalories delivered on post-operative day 5. Higher intestinal fatty acid binding protein was independently associated with subsequent development of suspected/definite necrotizing enterocolitis (4% increase in odds of developing necrotizing enterocolitis for each unit increase in intestinal fatty acid binding protein; p=0.0015). Conclusions: Intestinal fatty acid binding protein levels rise following infant cardiopulmonary bypass, indicating early post-operative enterocyte injury. Intestinal fatty acid binding protein was not associated with percent of goal enteral nutrition achieved on post-operative day 5, likely due to protocolized feeding advancement based on clinically observable factors. Higher intestinal fatty acid binding protein at 6hrs post-operatively was independently associated with subsequent development of necrotizing enterocolitis and may help identify patients at risk for this important complication.